Epigenome-wide analysis of DNA methylation reveals a rectal cancer-specific epigenomic signature. (September 2016) - Vymetalkova, Veronika; Vodicka, Pavel; Pardini, Barbara; Rosa, Fabio; Levy, Miroslav; Schneiderova, Michaela; Liska, Vaclav; Vodickova, Ludmila; Nilsson, Torbjörn K; Farkas, Sanja A
Aim: The aim of the present study is to address a genome-wide search for novel methylation biomarkers in the rectal cancer (RC), as only scarce information on methylation profile is available.Materials & methods: We analyzed methylation status in 25 pairs of RC and adjacent healthy mucosa using the Illumina Human Methylation 450 BeadChip.Results: We found significantly aberrant methylation in 33 genes. After validation of our results by pyrosequencing, we found a good agreement with our findings. The BPIL3 and HBBP1 genes resulted hypomethylated in RC, whereas TIFPI2, ADHFE1, FLI1 and TLX1 were hypermethylated. An external validation by TCGA datasets confirmed the results.Conclusion: Our study, with external validation, has demonstrated the feasibility of using specific methylated DNA signatures for developing biomarkers in RC.